2010
DOI: 10.1063/1.3431351
|View full text |Cite
|
Sign up to set email alerts
|

Local deposition of high-purity Pt nanostructures by combining electron beam induced deposition and atomic layer deposition

Abstract: Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 14 publications
0
82
0
Order By: Relevance
“…It has been found that the area selectivity of an ALD process toward specific materials, such as noble metals, can be achieved by tuning the process parameters, e.g. the temperature [40], the pressure [41], the nature of the coreactant or combinations thereof [36,37]. Key for these selective ALD processes of noble metals, such as Pt and Pd, is their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the area selectivity of an ALD process toward specific materials, such as noble metals, can be achieved by tuning the process parameters, e.g. the temperature [40], the pressure [41], the nature of the coreactant or combinations thereof [36,37]. Key for these selective ALD processes of noble metals, such as Pt and Pd, is their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] This so-called direct-write ALD approach combines area-selective ALD 23,24 with the directwrite patterning technique of electron beam induced deposition (EBID) 25,26 as illustrated in Fig. 1.…”
mentioning
confidence: 99%
“…O 2 dissociation usually prefers to take place on a metal surface, leading to the formation of active oxygen atoms to decompose and activate MeCpPtMe 3 molecules for the following reactions. [55][56][57] Kessels and coworkers reported that when the O 2 partial pressure decreased to 7.5 mTorr, the growth of Pt on Al 2 O 3 was inhibited. 36 No Pt growth was observed on Al 2 O 3 surface even after 600 cycles.…”
Section: Core Shell Catalytic Structuresmentioning
confidence: 99%
“…The dissociation of chemisorbed O 2 on the catalytic Pt group metal was a key step in the selective ALD mechanism. 55,57 The Pt ALD process at 7.5 mTorr could be considered as selective condition to Pd versus Al 2 O 3 substrate. Figure 2 shows the high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image and electron energy loss spectroscopy (EELS) line scan to confirm the Pd@Pt core shell structure fabricated with this selective ALD method.…”
Section: Core Shell Catalytic Structuresmentioning
confidence: 99%